Peran Pendidikan Islam terhadap Pembentukan Karakter Disiplin Peserta Didik - Unik Hanifah Salsabila; Annisa Septarea Hutami; Safira Aura Fakhiratunnisa; Wulan Ramadhani; Yuike Silvira (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2020)
This paper presents the role of islamic education in order to characterize the discipline of students. There are still many students in public schools underestimate matters related to discipline such as morals, manners, behavior or others. Therefore, islamic education is the key and the best solution in the prescription of disciplinary character in students where Islamic education is a process of deepening and appreciating knowledge in which there are Islamic values ​​given to students through the growth and development of their natural potential in order to arrive at equality and the perfection of his life. The research method used in this research is descriptive analysis by collecting data and sources to be analyzed, then interpreted critically and presented more systematically about islamic education to order the character of discipline in students. The results showed that the character of discipline in students can be formed by the role of islamic education, including through the provision of religious materials, habits, advice, admonitions, and exemplary examples from educators.